2015
DOI: 10.1080/00222895.2014.1003780
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Quiet Eye in Older Skilled Basketball Players

Abstract: There is mounting research to suggest that cognitive and motor expertise is more resistant to age-related decline than more general capacities. The authors investigated the retention of skills in medium-aged skilled (n = 14) and older-aged skilled (n = 7) athletes by comparing them with medium-aged less skilled (n = 15) and older-aged less skilled (n = 15) participants. Participants performed basketball free throws and dart throws as a transfer task under standardized conditions. Motor performance (accuracy) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The first QE study was carried out in the basketball free throw and found that elite players fixated the hoop early for an average of 972 ms on hits and 806 ms on misses, while their near-elite teammates averaged 400 ms on hits and 250 ms on misses (Vickers, 1996a, b). Subsequent studies have confirmed these results for high and lower skilled athletes, under conditions of anxiety and in QE training studies where novices are taught the QE characteristics of experts (Vickers, 1996a, b; Harle and Vickers, 2001; Wilson et al, 2009; Rienhoff et al, 2013; Fischer et al, 2015; Klostermann et al, 2017). A number of perceptual/cognitive and/or neural models have been proposed to explain these findings, for example, attention control theory (Eysenck et al, 2007; Wilson et al, 2009; Causer et al, 2011), ventral and dorsal processing (Vickers, 2012; Vickers and Willams, 2017), the inhibition hypothesis (Klostermann et al, 2014; Klostermann, 2019), and EEG/QE/ocular activity (Janelle et al, 2000a, b; Mann et al, 2011; Muraskin et al, 2016; Gallicchio et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…The first QE study was carried out in the basketball free throw and found that elite players fixated the hoop early for an average of 972 ms on hits and 806 ms on misses, while their near-elite teammates averaged 400 ms on hits and 250 ms on misses (Vickers, 1996a, b). Subsequent studies have confirmed these results for high and lower skilled athletes, under conditions of anxiety and in QE training studies where novices are taught the QE characteristics of experts (Vickers, 1996a, b; Harle and Vickers, 2001; Wilson et al, 2009; Rienhoff et al, 2013; Fischer et al, 2015; Klostermann et al, 2017). A number of perceptual/cognitive and/or neural models have been proposed to explain these findings, for example, attention control theory (Eysenck et al, 2007; Wilson et al, 2009; Causer et al, 2011), ventral and dorsal processing (Vickers, 2012; Vickers and Willams, 2017), the inhibition hypothesis (Klostermann et al, 2014; Klostermann, 2019), and EEG/QE/ocular activity (Janelle et al, 2000a, b; Mann et al, 2011; Muraskin et al, 2016; Gallicchio et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…These results are confirmed by , who chose to use ETG by ASL (at 29,97Hz), mentioning that in all conditions that precede jump shots, players stare at the target during a long enough period in order to reach success and that the efficiency of shooting depends on the duration and frequency of those fixations. Fischer et al (2015), who used ETG BY Arrington Research (at 30Hz), concluded that in perception motor tasks, such as in free throw, the level of expertise is maintained in older athletes, this due to the lack of significant differences, in this study, in the duration of QE between shootings or age groups in the analyzed tasks.…”
Section: Discussionmentioning
confidence: 59%
“…relationship between QE, anxiety and focus of attention Vine & Wilson, 2011;Wilson, 2010;; 2. occlusion of vision (de Oliveira, Huys, Oudejans, van De Langenberg, & Beek, 2007;de Oliveira, Oudejans, & Beek, 2006;Oudejans, Heubers, Ruitenbeek, & Janssen, 2012); 3. QE in jump shot and/or in free throw (de Oliveira et al, 2008;Fischer et al, 2015;Steciuk & Zwierko, 2015;Zwierko, Popowczak, Wozniak, & Rokita, 2016); 4. QE and jump shot with or without defense (Klostermann, Panchuk, & Farrow, 2017); 5. actions that precede the shooting (Oudejans, Karamat, & Stolk, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, little has been done in the maintenance of QE as athletes' age. In a series of studies, Rienhoff et al (2013) and Fischer et al, (2015) demonstrated that the role of QE in two different expertise groups and three different age groups might vary. In contrast to younger experts, showing the expected pattern of results, master athletes lose the QE and have shorter durations compared to novices in the same age group while still showing superior results.…”
Section: Development and Maintenance Of Qe In The Life-spanmentioning
confidence: 99%